Gartland Type III Supracondylar Fractures of Humerus with Closed Reduction and Percutaneous Fixation with K-Wires Children (Journal of Pakistan Orthopaedic Association, 2014)
Background: Supracondylar fractures are common skeletal injury in pediatric group at it comprises 50 to 70 % of elbow injury and are very potential for neurovascular injury between 5 to 10 years.Objective: To evaluate the results of Close Reduction with Percutaneous Fixation with k-wires in Gartland type III fractures.Design: Prospective studyMethods: 50 Patients Gartland type III selected through OPD and emergency department. Results were compared according Flynn criteria.Results: In our Study 35 Patients were male and 15 were Female Children 48 Patient were of extension type, 3 flexion type left side was involved in 45 Patients 5 in left. General age was 5 to 10 years. Maximum 5 to 8 years as the comparing the Flynn Criteria 40 were found excellent 5 Good, 3 were fair and 2 remain poor. Results in our study were excellent in terms of carrying angle and functional factors with loss motion. 3 were fair because of due to lost of their follow up Patient came late for observation in early days. During their visits in early stage 2 Patients came with elbow stiffness, 5 with pin tract infection 1 Patient was observed Cubitus varus with late presentation due to history of fall on operated limb treated with slab support. None have neuro vascular compromise. Union was achieved without any series complication.Conclusion: Close reduction and precutaneous fixation with cross K-wire in Gartland III fracture in children is effective way to prevent second procedure. K-wire fixation is preferred method because fracture configuration remains stable.